2012
DOI: 10.1371/journal.pone.0049985
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Prevention after Minor Stroke and TIA - Usual Care and Development of a Support Program

Abstract: BackgroundEffective methods of secondary prevention after stroke or TIA are available but adherence to recommended evidence-based treatments is often poor. The study aimed to determine the quality of secondary prevention in usual care and to develop a stepwise modeled support program.MethodsTwo consecutive cohorts of patients with acute minor stroke or TIA undergoing usual outpatient care versus a secondary prevention program were compared. Risk factor control and medication adherence were assessed in 6-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…The importance of hypertension control to prevent recurrent stroke and cardiac events has been emphasized, 23 and specific programs may improve the results of several aspects of secondary prevention. 24 However, frail older persons may not tolerate blood pressure lowering treatment to the same level as the healthier elderly or younger persons, and consequently, frail elderly need individual assessment of treatment strategies. 25 The prevalence of diabetes mellitus increased from 14%…”
Section: Lifestyle Indices (Table 3)mentioning
confidence: 99%
“…The importance of hypertension control to prevent recurrent stroke and cardiac events has been emphasized, 23 and specific programs may improve the results of several aspects of secondary prevention. 24 However, frail older persons may not tolerate blood pressure lowering treatment to the same level as the healthier elderly or younger persons, and consequently, frail elderly need individual assessment of treatment strategies. 25 The prevalence of diabetes mellitus increased from 14%…”
Section: Lifestyle Indices (Table 3)mentioning
confidence: 99%
“…Similarly, Kirk and colleagues17 found that community-based cardiac rehabilitation programmes for 12 patients post-TIA and minor stroke can be effective at reducing modifiable vascular risk factors. Reviews identifying effective components of rehabilitation following the diagnosis of a TIA and ‘minor’ stroke have begun to emerge,1012 , 31 but, to the authors’ knowledge, this is the first systematic review of the use of comprehensive rehabilitation programmes in the acute period (within 90 days) of the diagnosis of a TIA or ‘minor’ stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Some current guidelines8 , 9 advocate the promotion of early non-pharmacological secondary prevention after all cerebrovascular events but lack detail regarding effective methods of its delivery. There have been reports of lifestyle interventions post-TIA and minor stroke 1012. However, the authors have not identified any previous systematic reviews of the evidence relating to the effectiveness of early post-TIA rehabilitation or secondary prevention programmes that describe lifestyle interventions.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Leistner et al. 2012). Lastly, levels of patients’ satisfaction and quality of life – both increasingly recognized as important patient‐reported outcomes in acute stroke trials – were significantly higher in those receiving organized post‐stroke than usual care and therefore may have contributed to overall sufficient risk factor control in our study patients as previously suggested by the AVAIL registry (Bushnell et al.…”
Section: Discussionmentioning
confidence: 99%